ABC genotyping and putative virulence factors of Candida albicans clinical isolates - Moron, Llewelyn S. (Animo Repository, 2019)
Aims: Candida albicans is a diploid yeast which interacts with the host in a complex nature involving several fungal virulence factors and host's response. In this study, we investigated the different ABC genotypes of 26 clinical C. albicans isolates which is based on the presence of absence of transposable intron in the 25S rDNA, and the phenotypic expression of their virulence factors: phospholipase production, esterase production, haemolytic activities, biofilm formation, and white-opaque switching. Methodology and results: In this study, we investigated the ABC genotypes of 26 clinical C. albicans isolates, and the phenotypic expression of their virulence factors. The C. albicans isolates were tested for their in vitro abilities in exhibiting the following virulence factors: phospholipase, biofilm, esterase, hemolysin and phenotypic switching. Phospholipase activities and biofilm formation were detected in 57.7% and 65.38% of the isolates, respectively. All of the isolates showed phenotypic white-type colony, while none showed esterase and hemolytic activities. ABC genotyping revealed that 50% of the isolates were grouped under Genotype A, followed by Genotype C (42.3%), and B (7.69%). Conclusion, significance and impact of study: This study provides information in regard to virulence potential and the ABC genotype of C. albicans from the Philippines. © 2019, Universiti Sains Malaysia.